Price Perceptions And Facilities On Patient Satisfaction Mediated By Dentist Street Dental Clinic Service Quality - Haryono, PM. Budi; Purnama, Ekas Desy; Lestari, Sutji (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2024)
In an increasingly competitive health service industry, patient satisfaction is a key factor that needs to be considered by clinics or hospitals. Patients are now increasingly aware of the importance of service quality, so clinics must make strategies and innovations to improve service quality to achieve patient satisfaction. Some of the factors that affect patient satisfaction include price perceptions, supporting facilities, and service quality. Reasonable prices according to service quality, good and comfortable facilities, and high service quality such as professionalism, good communication, and availability of information can increase patient satisfaction. Patient satisfaction is very important because satisfied patients tend to provide positive references and return to use the clinic's services, thereby increasing the number of new patient visits. This study focuses on the effect of perceived price, facilities, and service quality on patient satisfaction at the Dentist Street Kayu Manis Dental Clinic, East Jakarta. This clinic is one of the oral health service providers that continues to strive to improve the quality of its services to maintain patient trust and satisfaction amid increasingly fierce competition. Located at the Dentist Street Dental Clinic, Kayu Manis, East Jakarta, totalling 80 (Eighty) people and all members of the population as well as samples so that this research is a census study. The results of this analysis show that all indicators used in this study are valid and reliable. This study uses a Structural Equation Modeling (SEM) approach based on Partial Least Square (PLS) using SmartPLS 3.3 software. This study provides evidence of a positive and significant effect